PERANCANGAN SISTEM INFORMASI KAMPUS TERINTEGRASI DI LINGKUNGAN POLITEKNIK LP3I MEDAN - Iswandi Idris; Humala Napitupulu; Nazarudin Matondang (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2015)
This study was conducted to obtain Integrated Information System（IIS）in Politeknik LP3I Medan (PLM), Analysis of the cost of an integrated information system design and integrate information systems in the campus environment. The subjects of the study a total of 336 samples. Cronbach Alpha reliability test values obtained 0.753 or reliable (reliability) is high. Correlation Test Double (R) of 0.247 or lower of a relationship between the independent variable on the independent variable. Test R2 (R Square) of 0.61 or (61%). F calculated > F Table (2,663> 1.9667), then H1 is accepted, it means There is significant effect between 8 independent variables together to SIT (dependent). T test showed 2 independen variabels rejected H0 means academic documentation process speed and sophistication of communication tools, collaboration and coordination between units in PLM partly no significant effect on the integrated information system. Using cost-benefit ratio analysis (Benefit Cost Ratio, BCR) then the total benefit greater than the total cost of 1 is 4.66 to SIT investment can be applied, and further integration of the SI strategy is applied. Scheme design of information systems will be easier to implement with a top-down and bottom-up, carried out in stages, starting from planning, analysis, design, preparation of DFD, design arsitekktur SIT.